Stock Price Prediction Model On Automotive Companies And Its Components Listed On The Indonesia Stock Exchange - Rulliyani, Rulliyani; Subiantoro, Nur; Nasib, Nasib; Rinanda, Teja (Publisher Cv. Inara, 2022)
The purpose of this study is to analyze whether economic value added and profitability (ROA) can affect prices for automotive companies and their components on the Indonesia Stock Exchange. This study uses 12 automotive companies and their components listed on the Indonesia Stock Exchange in 2014-2019. Methods of collecting data by means of documentation or literature study. The sampling technique in this study used purposive sampling and the ardl panel research method. Based on the results of the study, it can be concluded that there are nine automotive companies on the Indonesian stock exchange, namely; PT. Astra International, Tbk; PT. Astra Otoparts, Tbk; PT. Indo Kordsa, Tbk; PT. Goodyear Indonesia, Tbk; PT. Gajah Tunggal, Tbk; PT. Multi Prima Sejahtera, Tbk; PT. Multistrada Directions Sarana, Tbk; PT. Nippres, Tbk; PT. Prima Alloy Steel Universal, Tbk, Economic Value Added and Profitability variables have a significant influence on stock prices. While in two companies, namely PT. Indomobil Sukses Internasional, Tbk and PT. Selamat Sempurna, Tbk, only the Economic Value Added variable has a significant influence on stock prices. And in one company, namely PT. Indospring, Tbk only profitability variables that significantly affect stock prices. In general, Economic Value Added and Profitability are leading indicators for controlling stock prices. However, on a panel basis, neither of the two has been able to become a leading indicator for controlling share prices in automotive companies and their components on the Indonesian stock exchange. This is because the two variables have not provided a stable influence on a panel basis for all companies studied as automotive companies and their components on the Indonesian stock exchange.